INFLUENCE OF FISH MEAL REDUCTION, ALGAE ADDITION, AND ENZYME USE IN SHRIMP FEEDS ON THE TISSUE COMPOSITION OF Litopenaeus vannamei - Sebastian Kaspers; Andreas Kunzmann (Indonesian Aquaculture Journal, 2012)
At the Leibniz-Center for Tropical Marine Ecology in Bremen, Germany, shrimps (Litopenaeus vannamei) fed feeds with reduced fish meal content, algae and enzyme additions were analysed for their tissue composition. Contents of protein, glycogen, total lipid, linoleic acid (LA), alpha linolenic acid (ALA), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) of the shrimp abdomen and of the respective feeds were determined. Reduction of fish meal (FM) content in shrimp feed and its substitution with “mash” (grain distillery waste-”Schlempe”), corn gluten, pea or coarse colza meal did not influence the tissue composition. Additional inclusion of an algae mixture out of Spirulina spp., Phaeodactylum spp., and Tetraselmis spp. to shrimp feeds as well as the single inclusions of Phaeodactylum spp. or Spirulina spp. had no effect on the tissue composition. Furthermore no improvement of the quality of the shrimps due to an enhanced digestibility of mash by enzymes (mixture of corolase, phytase, xylanase) could be detected. In contrast the quality of shrimps seemed to be negatively affected by enzymes in this study. These findings could contribute to making shrimp aqua farming more economic as reduction of feed costs without reduction of the quality of the shrimps would be a large benefit.